Analysis of hybrid arch and cable-stayed bridge - Hasmida, Noordin (2015)
ectives of this thesis is to study the principal component of cable-stayed and arch bridge with hybrid arch bridge and secondly to investigate the structural behavior between normal arch and cable-stayed bridge. The thesis discussed the structure behavior between these three bridges model to obtain the most effective bridge. The structure two-dimensional model was developed using computer programmed, LUSAS 14 Bridge. The models were analyzes using the linear static analysis which are displacement, stress and bending moment in each bridge main components. There were three arch bridge models, three cable-stayed bridge fan system models, three cablestayed harp system models and one hybrid arch bridge model. Every model is 600m total long with 300m main span and 150m side span. The loading applied was dead load and live load only. The first analysis is to obtain the stronger arch and cable-stayed bridge. The result obtained that the arch bridge with rise-to-span ratio 1:5 and cablestayed fan system with 80m of pylon height was the stronger model. Finally, the pure arch and cable-stayed bridge were compared with hybrid arch bridge analysis. Result from LUSAS shows that, hybrid arch bridge was the most effective bridge for long bridge because it has lower displacement, stress and bending moment compared to pure arch and cable-stayed bridge. The structure behavior of hybrid arch bridge is seemed to be stronger. The deck of hybrid arch bridge is support by pylon and arch rib make it more durable in cater the loading applied as compared to pure arch and cable-stayed bridge